2019
DOI: 10.3758/s13414-019-01821-5
|View full text |Cite
|
Sign up to set email alerts
|

Probing the time course of facilitation and inhibition in gaze cueing of attention in an upper-limb reaching task

Abstract: Previous work has revealed that social cues, such as gaze and pointed fingers, can lead to a shift in the focus of another person's attention. Research investigating the mechanisms of these shifts of attention has typically employed detection or localization button pressing tasks. Because indepth analyses of the spatio-temporal characteristics of aiming movements can provide additional insights into the dynamics of the processing of stimuli, the current study used a reaching paradigm to further explore the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 42 publications
1
34
4
Order By: Relevance
“…In addition, many studies have found that for peripheral cues, when the SOA is around 300 ms, the RT for the cued target is signi cantly longer than for the uncued target, that is, the inhibition of return (IOR), whereas the cueing effect of central cues is longer in duration and IOR occurs later, especially for gaze cues [46,47]. Frischen and Tipper [48] found that the IOR was only exhibited under gaze cues when the SOA was 2400 ms. Yoxon et al [49] also used a 50% validity gaze cue and set up seven SOAs: 100, 250, 400, 700, 1000, 1700, and 2400 ms. They found that at SOAs of 250, 400, 700, and 1000 ms, signi cant cueing effects were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have found that for peripheral cues, when the SOA is around 300 ms, the RT for the cued target is signi cantly longer than for the uncued target, that is, the inhibition of return (IOR), whereas the cueing effect of central cues is longer in duration and IOR occurs later, especially for gaze cues [46,47]. Frischen and Tipper [48] found that the IOR was only exhibited under gaze cues when the SOA was 2400 ms. Yoxon et al [49] also used a 50% validity gaze cue and set up seven SOAs: 100, 250, 400, 700, 1000, 1700, and 2400 ms. They found that at SOAs of 250, 400, 700, and 1000 ms, signi cant cueing effects were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Most existing research on the orienting of attention in social cueing uses discrete buttonpressing tasks and, as such, has only been able to examine RTs and/or response accuracy in choice tasks. Deviating from this tradition, Yoxon et al (2019) used an upper-limb reaching task to examine the facilitatory and inhibitory effects of gaze cues on attention and action execution.…”
mentioning
confidence: 99%
“…In Experiment 1 of Yoxon et al (2019), the centrally presented model head remained fixating on the target until the end of the participant's reaching movement. In contrast, in Experiment 2, the gaze cue only lasted for 150 ms before the eyes of the model returned to a neutral gaze direction.…”
mentioning
confidence: 99%
See 2 more Smart Citations